Buddhists, shamans, and Soviets: rituals of history in post-Soviet Buryatia - Quijada, Justine B. (Oxford University Press, 2019)
Introduction: if you want to have a future you have to have a good relationship to your past -- An inauguration for Etigelov: multiple genres of history in Buryatia -- Soviet selves: victory day -- City day, hospitality, the friendship of the peoples and multikulturalizm -- Etigelov at Maidari: the once and future buddhist -- Opening the center, opening the roads -- Porous selves: Yuri's initiation